2016
DOI: 10.1024/0939-5911/a000444
|View full text |Cite
|
Sign up to set email alerts
|

Der Epidemiologische Suchtsurvey 2015

Abstract: Zusammenfassung. Ziel: Der vorliegende Beitrag beschreibt die Methodik und das Studiendesign des Epidemiologischen Suchtsurveys (ESA) 2015. Methodik: Zielpersonen des ESA waren deutschsprachige und in Privathaushalten lebende Personen im Alter zwischen 18 und 64 Jahren. Die Ziehung der Personenstichprobe erfolgte auf Basis der Einwohnermelderegister disproportional zur Verteilung der Geburtsjahrgänge in einem zweistufigen Zufallsverfahren. Die Befragungen wurden schriftlich, telefonisch und online durchgeführt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 14 publications
0
19
0
4
Order By: Relevance
“…The results of the present study are further limited, because of the collection of self-reported data which might be biased due to socially desirable answers [17]. Additionally, certain subgroups, which are known for increased rates of substance consumption, i.e.…”
Section: Limitations and Strengthsmentioning
confidence: 84%
See 1 more Smart Citation
“…The results of the present study are further limited, because of the collection of self-reported data which might be biased due to socially desirable answers [17]. Additionally, certain subgroups, which are known for increased rates of substance consumption, i.e.…”
Section: Limitations and Strengthsmentioning
confidence: 84%
“…The average age of the participants was 42.3 years (95%-CI = [42.0; 42.7). For further information on methods and design of the ESA 2015 please see Piontek and colleagues [17].…”
Section: Study Design and Samplementioning
confidence: 99%
“…A marked increase (e. g., 2009/2010 vs. 2015/2016) of methamphetamine use in HIV-positive MSM was here observed. Pres-ent figures seem to be considerably higher than those observed in a survey (Epidemiological Survey of Substance Abuse) carried out in the German general population (▶ Table 1) [11,12]. In this study, a representative sample of German residents was asked about their substance use with the help of interviews administered by mail, telephone, or internet, in contrast to the 1:1 interviews carried out here.…”
mentioning
confidence: 71%
“…Insgesamt waren in der Stichprobe 49,6 % Frauen (n = 5090) und 50,4 % Männer (n = 4114) mit einem durchschnittlichen Alter von 38,3 Jahren (SD = 14,7) vertreten. Für eine detailliertere Beschreibung von Methodik und Design des ESA 2015 wird auf Piontek, Kraus, Gomes de Matos und Atzendorf [10] verwiesen.…”
Section: Studiendesign Und Stichprobeunclassified
“…Limitationen der vorliegenden Untersuchung beinhalten mögliche Verzerrungen aufgrund von Selbstauskünften der Studienteilnehmer, welche zusätzlich durch den Erhebungsmodus beeinflusst wurden [10,23]. Ferner muss beachtet werden, dass lediglich Personen im Altersbereich von 18 bis 64 Jahre in die Grundgesamtheit der Erhebung einbezogen wurden.…”
Section: Diskussionunclassified